2022
DOI: 10.1002/jper.21-0423
|View full text |Cite
|
Sign up to set email alerts
|

Biome‐microbiome interactions in peri‐implantitis: A pilot investigation

Abstract: Background Dental implants replace missing teeth in at least 100 million people, yet over one million implants fail every year due to peri‐implantitis, a bacterially induced inflammatory disease. Our ability to treat peri‐implantitis is hampered by a paucity of information on host‐microbiome interactions that underlie the disease. Here, we present the first open‐ended characterization of transcriptional events at the mucosal‐microbial interface in the peri‐implant crevice. Methods We simultaneously sequenced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…It is quite interesting that despite so many previously described similarities between periodontitis and peri-implantitis, as Rakic pathogenesis of periodontal disease (Marchesan et al, 2020). In peri-implantitis, Ganesan et al (2022) have reported the increased in NLRP2, NLRP8, and NLRP12. The current study has also identified NLRP3 inflammasome in peri-implantitis.…”
Section: Patient-level Variablementioning
confidence: 99%
“…It is quite interesting that despite so many previously described similarities between periodontitis and peri-implantitis, as Rakic pathogenesis of periodontal disease (Marchesan et al, 2020). In peri-implantitis, Ganesan et al (2022) have reported the increased in NLRP2, NLRP8, and NLRP12. The current study has also identified NLRP3 inflammasome in peri-implantitis.…”
Section: Patient-level Variablementioning
confidence: 99%
“…68 In biofilm surrounding implants, differences from normoglycemia were reported to regards mostly the deep pockets, 69 more yeasts were found in T2D, 69 and a 4-to 200-fold increase was reported in upregulated gene expression toward a non-healing wound by suppressing the commensals' protective effect enhancing epithelial integrity. 70 Similar mechanisms are found around implants where hyperglycemia causes changes in the composition of the microbiome that interrupts the homeostasis between the bacteria and the host defense system. In brief, chronic hyperglycemia (Figure 10):…”
Section: Biologic Plausibilitymentioning
confidence: 83%
“…Moreover, due to impaired metabolic and immune regulation, T2D patients are reported to be more susceptible to such microbiome shifts (dysbiosis) than health individuals 68 . In biofilm surrounding implants, differences from normoglycemia were reported to regards mostly the deep pockets, 69 more yeasts were found in T2D, 69 and a 4‐ to 200‐fold increase was reported in upregulated gene expression toward a non‐healing wound by suppressing the commensals' protective effect enhancing epithelial integrity 70 …”
Section: Impact Of Systemic Driversmentioning
confidence: 99%
“…More pro-inflammatory macrophages implied increased expression of inflammatory cytokines (e.g., IL-1, IL-6, and IL-8) and MMP, which may lead to more prolonged inflammation ( Wilkinson et al, 2019 ). Genes involved in apoptosis, mucosal migration and intercellular communication were reported to be upregulated 4-fold–200-fold when inflammation around the implant increased, which simultaneously slowed the rate of wound healing ( Ganesan et al, 2022 ).…”
Section: The Mechanisms Of Diabetes Leading To Impaired Soft Tissue Sealmentioning
confidence: 99%